LANDREFORM DAN PASANG SURUT PERKEMBANGANNYA DARI MASA KE MASA - Ahyuni Yunus (Fakultas Hukum Universitas Muhammadiyah Palu, 2019)
The Landreform concept experiences variations in development over time in line with the function of land as a factor of production, a source of wealth, a symbol of status, and a source of social or political influence. The commitment to run the Landreform program eventually returned to the state administrators to make it happen. Landreform agenda cannot run without state participation, because Landreform is a state agenda. Implementing land reform without effective state participation will only be an idea. The history of our nation is enough to prove that the ebb and flow of the implementation of land reform is strongly influenced by the ebb and flow of participation of state administrators. However, it cannot be denied that land reform in Indonesia whose aim is none other than the aim of the LoGA itself, has always been a reference for land law in our country including reform efforts in the field of land. The history of the Indonesian people, in line with or in line with the journey of land reform. Land reform in Indonesia has entered 3 (three) periods, namely: the Old Order, New Order and reformation periods. This proves that the land reform program is a required program. Keyword: Landreform, Development